Methods of treating or preventing conditions associated with opioid withdrawal or opioid recurrence - TOMES, CHARLES, F (2024)
The present disclosure relates to methods of treating or preventing a condition (e.g., a symptom associated with opioid withdrawal or opioid recurrence) in a subject comprising administering to the subject a therapeutically effective amount of teempanide, a pharmaceutically acceptable salt thereof, or a prodrug thereof. 本公开涉及治疗或预防受试者的病症(例如，与阿片类物质戒断或阿片类物质复发相关的症状)的方法，所述方法包括向所述受试者施用治疗有效量的替占帕奈、其药学上可接受的盐或其前药。